International Legal Regulations Concerning Launching of Russian Anti-Satellite Weapon Missiles Reviewed in Space Law Perspective - Mohammad Rifki Daud; Amanda Adelina Harun (Estudiante Law Journal, 2022)
The development of weapons technology is currently very advanced and competitive, one of which is the Anti-Satellite weapon (ASAT) technology. ASAT has become a real threat to the sustainability of the space environment, this is because ASAT has the potential to damage international peace and security, trigger an arms race, and increase the amount of space debris orbiting the earth. The absence of regulations that specifically regulate ASAT makes countries feel free to conduct anti-satellite missile test launches. For example, in 2021 Russia conducted an ASAT test targeting the Cosmos-1408 satellite. Using normative juridical research and research approaches with statute approach, case approach, and analytical approach, the author wants to study and analyze international legal arrangements regarding the launch of Anti-Satellite Weapon (ASAT) missiles and the legal consequences against Russia as the country that launches Anti-Satellite Weapon (ASAT) missiles. Based on the results of the study, the researchers found that there were no regulations specifically limiting ASAT, but the regulation in question should have been contained in the Outer Space Treaty 1967 as the basis for regulating all activities related to space, then further legal consequences against Russia for launching anti-missile missiles. -satellite, namely Russia is obliged to be responsible in terms of responsibility and liability in terms of liability and is strengthened by the principle of liability based on fault as stated in the Liability Convention 1972.